The Effect of Age on the Haptic Horizontal-Vertical Curvature Illusion With Raised-Line Shapes - Ballesteros, Soledad; Mayas, Julia; Reales, José Manuel; Heller, Morton (Developmental neuropsychology, 2012)
In the present study, we investigated the effect of age in the haptic horizontal-vertical curvature illusion from adolescence to old age. Blindfolded participants explored raised-line convex curves with one finger and two fingers (Experiment 1). They judged the size of the curves (horizontal/vertical), using two sliding rulers. The results suggest that young and older haptic explorers overestimated the vertical. Adolescents did not show the haptic illusion. In Experiment 2, adolescents performed the task visually showing a stronger horizontal-vertical illusion. The findings suggest that the illusion develops later in touch than in vision. The theoretical implications of the results are discussed.